Tanggung Jawab Hukum Pelaku UMKM yang Tidak Mencantumkan Tanggal Kedaluwarsa pada Produk Makanan Kemasan - Miftakhul Janah; Ayub Torry Satriyo Kusumo (SENTRI: Jurnal Riset Ilmiah, 2026)
In the current of globalization, MSMEs are increasingly developing with a variety of attractive packaged food products. However, some business actors have not yet realized the importance of including information on the packaging, especially the expiration date. The absence of this information can harm consumers because consumers do not know whether the product is still suitable for consumption. This study aims to determine the legal responsibility of MSME actors who do not include an expiration date on packaged food products. This study uses a normative juridical approach method. The results of the study show that to ensure the quality and safety of food circulating in the community, business actors are required to comply with applicable regulations, including the inclusion of product information labels, especially the expiration date. If food products are distributed without such labels, business actors can be subject to sanctions for intentional or negligent actions. Article 3 paragraph (2) of PP No. 69 of 1999 stipulates that food labels must include the expiration date, month, and year. If ignored, business actors are subject to administrative sanctions such as written warnings, distribution bans, product recalls, destruction, production cessation, a maximum fine of 50 million rupiah, and even revocation of business permits. In addition, Article 8 paragraph (1) letter g in conjunction with Article 62 paragraph (1) of Law Number 8 of 1999 states that violations of the obligation to include an expiration date can be subject to a maximum prison sentence of 5 years/a maximum fine of 2 billion rupiah as a form of legal protection for consumers.